Analysis of Supportive Lower Structure Building on Overpass Construction In The Sumatera Trans Toll Road - Lidyawati, Dian Erlisa; Adha, Idharmahadi; Purwadi, Ofik Taufik (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2020)
Every light or heavy load construction recquires a supportive foundation, the foundation must be calculated to be able to guarantee the stability of the building to its own weight, building loads and external forces. Pillar foundation is used as a building foundation when the land under the building does not provide sufficient carrying capacity to carry the weight of the building and its load. This research was carried out on one of the bridges on the Trans Sumatra Toll Road. A pillar foundation is used to the toll road project. The purpose of this research is to determine the bearing capacity of the foundation on the pier and abutment from the results of load on the upper construction. Based on the results of the carrying capacity of abutment is obtained 60 cm diameter of pile with 6 pieces, and the bridge’s pillar is 60 cm of pile 15 pieces. While the main reinforcement diameter is 22 mm as much as 6 pieces, with Ø10 strap and 250 mm distance.  Keywords: Foundation, Pillar, Pile, Pile Carrying Capacity